Contractual Issues for Hydropower Construction in Nepal - Neupane, Abhushan (Hydro Nepal: Journal of Water, Energy and Environment, 2018)
Nepal is located at the foot of the Himalayas and has numerous perennial rivers flowing from North to South, making it an ideal place for production of massive scale of hydropower. Hence, there are many hydropower projects in construction phase, but they are facing several contractual issues such as, contractual inefficacy of the parties, payment problems, Force Majeure and claims handling mechanism. In order to build the capacity of existing contract personnel working in various projects, it is high time for the stakeholders of Nepalese construction industry to train their human resources to the required standard, such that they can properly prepare, assess and handle the contractual issues that may arise, in the international standard. HYDRO Nepal Journal Journal of Water, Energy and Environment Issue: 23 Year: 2018